Exploring Predictors of Community Participation Among Young Adults with Severe Disabilities. (September 2019) - Lee, Hyunjoo; Morningstar, Mary E.
A secondary analysis of data from the National Longitudinal Transition Study–2 (NLTS2) was conducted to examine predictors associated with improved postschool community participation of young adults with severe disabilities. Multidimensional item response theory was used to establish criterion and predictor constructs and examine predictive relationships between these constructs. Results identified two outcome constructs (community involvement, social engagement) and four predictors (functional skills, classroom behaviors, participation in social networks, access to vocational programs) establishing good model fit. Participation in social networks while in school was a strong predictor of both community involvement and social engagement. Functional skills of young adults predicted postschool community involvement. Implications for future research and practice promoting and supporting community participation are discussed.